CHANGES IN THE HIP IN YOUTH HOCKEY PLAYERS OVER 5 SEASONS. Issue 4 (1st February 2017) - Briggs, Karen; Philippon, Marc; McNamara, Shannen; Ho, Charles
Abstract : Background: It has been reported that relative to other sports participants, ice hockey players suffer from cam femoroacetabular impingement (FAI) in higher numbers. Alpha angles have been reported to increase with the likelihood of symptomatic FAI. It is unclear how alpha angle and other factors related to FAI change over early childhood years. Objective: Track youth hockey players over 5 years and determine if factors associated with FAI increased as they aged and increased skating time. Design: Screening. Setting: Youth club. Patients (or Participants): 16 asymptomatic youth ice hockey players. All players started in the peewee(ages 10 to 12) division and moved up in divisions over the 3 years. Interventions (or Assessment of Risk Factors): Clinical hip examination consisting of the FABER test, impingement testing, and measurement of hip internal rotation. An MRI was taken and the hip alpha angle was measured and labral tears were documented. Main Outcome Measurements: Alpha angle and labral tear on MRI Results: These youth hockey players played an average of 42 weeks/year Players had significantly increased alpha angle by year 3 of screening. The average alpha angle at year 1 was 56(range 45 to 63), year 2 was 59 (range 52 to 68), year 3 was 75 (range 64 to 88), year 4 was 75 and year 5 was 78. By year 5, 14/16 had asymptomatic labral tears. There were no significant changes in internal rotation over the 5 years. There was a trend toward decreased internal rotation in goalies. Conclusions: Young ice hockey players show increasing alpha angles and development of asymptomatic labral tears. Stresses inherent to ice hockey likely enhance the development of a bony overgrowth on the femoral neck contributing to cam FAI.